Peningkatan Minat Belajar SBdP Siswa dengan Pembelajaran Model Project Based Learning di SD Negeri Balekambang - Wiradharma, izwar (Sangkalemo : The Elementary School Teacher Education Journal, 2024)
AbstractThis research was carried out to increase student interest in SBdP lessons in class VI students at SD N Balekambang using project based learning (PjBL). The method used was classroom action research. The subjects of this research were class VI students with a total of 12 students and was carried out in 2 cycles. The data collection method used is an observation sheet to measure students' interest in learning. understanding. The data analysis technique used is descriptive statistics. Based on the results of research that has been carried out by applying the project based learning (PjBl) model in learning during research, it can increase student interest in SBdP learning activities in the learning process in cycle I. The data obtained was 41.%7 or 5 students who got good scores. and in the second cycle it increased to 83.3. Students who get good scores. So it can be said that this research was successfulKeywords: Interest, SBdP, Project Based Learning.